(untitled) (Pelita Perkebunan (a Coffee and Cocoa Research Journal), 2023)
Cocoa production remains an important player in Ghana’s economy. Over the years, there has been a shift from the traditional cocoa agroforestry system to full-sun cocoa production. Due to extreme exposure to high temperatures, sunlight and drought, the photosynthetic mechanism of cocoa is altered, reducing yield. Cocoa agroforestry provides economic, social, and ecological benefits and plays subsistence functions such food and fuelwood. The study was carried out to assess cocoa agroforestry systems based on shade and its effect on yield in the Offinso Municipality of Ghana. The study aimed to identify the types of cocoa agroforestry systems based on shade, determine the factors affecting cocoa agroforestry systems and assess the impact of shade regime on cocoa yield in the municipality. Purposively cocoa farmers were randomly and were adminis- tered with questionnaires. The study revealed that farmers in the Offinso Municipality practice all types of cocoa agroforestry systems (full sun, low shade, medium shade, and heavy shade). The cultivation of cocoa under medium shade (15–18 trees ha-1) proved to be beneficial and essential for the long-term production of cocoa. The medium-shade cocoa recorded a higher average yield of 1576 kg ha-1. Six common shade trees identified include Terminalia superba (ofram), Ricinodendron heudelotii (wawa) and Chlorophora excelsa (odum). Some challenges faced as a result of practicing the cocoa agroforestry system were pest infestation and diseases such as that of the black pod. Cocoa agroforestry still holds the key to sustainable future outputs in cocoa production as it drives the realization of SDG goal 13 (climate action). There is therefore the need to educate farmers on managing their farms with trees for optimum ecological and economic benefits.